Flood frequency analysis for Sarawak using Weibull, Gringorten and L-Moments formula - Onni Suhaiza, Selaman, Dr.; Salim, Said, Prof. Dr.; Frederik, Josep Putuhena, Prof. Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/